2018
DOI: 10.1038/s41598-017-18893-8
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Human Migrations to and through Jammu Kashmir- India were not of Males Exclusively

Abstract: Jammu and Kashmir (J&K), the Northern most State of India, has been under-represented or altogether absent in most of the phylogenetic studies carried out in literature, despite its strategic location in the Himalayan region. Nonetheless, this region may have acted as a corridor to various migrations to and from mainland India, Eurasia or northeast Asia. The belief goes that most of the migrations post-late-Pleistocene were mainly male dominated, primarily associated with population invasions, where female mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 71 publications
4
17
0
Order By: Relevance
“…Even if one increases both amplitudes, keeping the two of them unequal with f ̸ = 1 limits the maximum velocity. On the other hand, when f = 1 the maximum, velocity can be as close to c as one wishes, all depending on the choice of the proper common mode amplitudes, whose extended range seen in the figure is compatible with the intensities generated in current petawatt and future exawatt highfrequency lasers [24] and self-focused infrared lasers of relativistically high intensities [25]. Color graded map for Gv π in terms of laser and wiggler amplitudes.…”
Section: Resonant Trappingmentioning
confidence: 62%
“…Even if one increases both amplitudes, keeping the two of them unequal with f ̸ = 1 limits the maximum velocity. On the other hand, when f = 1 the maximum, velocity can be as close to c as one wishes, all depending on the choice of the proper common mode amplitudes, whose extended range seen in the figure is compatible with the intensities generated in current petawatt and future exawatt highfrequency lasers [24] and self-focused infrared lasers of relativistically high intensities [25]. Color graded map for Gv π in terms of laser and wiggler amplitudes.…”
Section: Resonant Trappingmentioning
confidence: 62%
“…The region is being bordered by countries such as Pakistan in the west, Afghanistan in the north-west and China in the north-east (Bhasin and Nag, 2002a). Topographically, J&K is divided into three main isolated divisions, namely Jammu, Kashmir, and Ladakh (Sharma et al, 2018). The region is characterized by tough mountainous terrains that have rendered geographical isolation of its heterogeneous population.…”
Section: Jammu and Kashmir: A Model Population For Studying Rare Genementioning
confidence: 99%
“…According to the Population Census of India -2011, Muslims (68.31%) constitute the major inhabiting population strata in J&K, followed by Hindus (28.44%), Sikhs (1.87%), Christians (0.28%), Jains (0.02%) and others (0.17%). The contemporary population of J&K speaks languages belonging to three different linguistic families -the Indo-European, Tibeto-Burman (in Ladakh) and various dialect of Dardic (in Kashmir) from Indo-Aryan language group (Sharma et al, 2018). These population groups usually reside in small, geographically and socially isolated pockets since many centuries and are variably reinforced by their societal or religious customs to practice endogamy or consanguinity.…”
Section: Population Architecture Of Jandkmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations with an allelic frequency greater than 5% in Gujarati Indians from Houston (GIH) and Western European Ancestry (CEU) as it has been observed that genetic makeup of the studied population is similar to Europeans (16). The studied genes and variants with their putative role and annotations are summarized in the Table S3.…”
Section: Candidate Gene and Snp Selectionmentioning
confidence: 99%